Antioxidant Capacity, Phenolic and Organoleptic Profiles of Beers Maturated with Bilberries - Petar Nedyalkov; Vesela Shopska; Giuseppe Perretti; Maria Kaneva (Fermentation, 2025)
Beer is probably one of the oldest alcoholic beverages, and regarding consumption, is third place after water and tea. Due to the consumer’s pursuit of novel tastes and aromas, craft brewers are trying to meet the consumer’s need, so brewing beer with a fruit addition is the new twist. Fruit incorporation into the brewing process leads to alterations in the sensory properties and chemical composition of beers, but most of the articles published on this topic are mainly concentrated on beers with fruits different from bilberries. The data on bilberry beers are still scarce. Therefore, our projects are based in this field to investigate beer production with bilberries. In our previous research, we found interesting changes in the protein profile of bilberry beers with different original extracts. Therefore, the aim of this study was to investigate the influence of the original extract of beer maturated with bilberries on the phenolic profile (determined by HPLC analysis), the antioxidant capacity (measured by the ABTS, DPPH, FRAP, and CUPRAC methods), and sensory characteristics. The reported data can contribute to the development and production of bilberry beers with high antioxidant capacity and pleasant sensory properties.